Effects of porcine circovirus type 2 vaccination, biofuel co-products, and dietary enzymes on finishing pig performance under field conditions - Jacela, Jay Yanoria (Kansas State University, 2009)
A total of 9,979 pigs were used in 11 experiments to quantify production responses under field conditions in growing pigs to PCV2 vaccination, biofuel co-products and dietary supplemental enzymes. Experiments 1 and 2 were conducted to determine the efficacy of a commercial 2-dose Porcine Circovirus Type 2 (PCV2) vaccine. Growth performance and mortality (P < 0.05) of vaccinated pigs improved compared to non-vaccinated pigs in both experiments with the vaccine causing a greater increase in ADG in vaccinated barrows than vaccinated gilts in Exp. 2. Experiment 3 compared the efficacy of 1-dose and 2-dose commercial PCV2 vaccines, where vaccinated pigs had greater ADG (P < 0.05) than vaccinated pigs regardless of vaccine type. The 2-dose group was heavier (P < 0.05) than the control group while the 1-dose group was intermediate. Therefore, PCV2 vaccines were efficacious under field conditions. Experiments 4, 5, and 6 were conducted to evaluate de-oiled corn dried distillers grains with solubles (dDGS) in grow-finish pigs. In Exp. 4, analyzed CP and AA content were higher, but lysine digestibility and energy content were lower in dDGS than traditional dried distillers grains with solubles (DDGS). In Exp. 5, 0 to 30% dDGS in nursery diets did not affect growth performance (P > 0.52). In Exp. 6, 0 to 30% dDGS reduced (linear; P < 0.01) ADG and ADFI, tended to improve (linear; P > 0.07) G:F, decreased (linear; P < 0.01) carcass yield, and increased (linear; P < 0.01) fat iodine values. Experiment 7 was conducted to determine the AA digestibility and energy concentration of novel high-CP distillers co-products from corn (HPC-DDG) and sorghum (HPS-DDGS). Digestibility of AA was higher for HPC-DDG but lower in HPS-DDGS than traditional DDGS. Both co-products had lower energy than traditional DDGS. Finally, Exp. 8, 9, 10, and 11 were used in a meta-analysis to evaluate supplementary dietary enzymes in pigs. Supplemental enzymes, alone or in combination, did not improve grow-finish pig performance (P > 0.58) regardless of dietary DDGS level. In conclusion, these experiments provide important empirical data to quantify production responses of various interventions and dietary ingredients under actual field conditions.
Keywords: Porcine circovirus type 2; Vaccine; Dried distillers grains; Dietary enzymes; Growing-finishing pigs; Growth performance; Agriculture, Animal Culture and Nutrition (0475); Biology, Veterinary Science (0778)